THE NATURE OF WAR - Gogrichiani Jumber (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The present work presents the ongoing conflicts in the history of mankind and ways to solve them. The first humans began their existence with conflict. Over the millennia, the main goal and purpose of war has not changed - to arrange one's own well-being at the expense of human life. Countries are destroyed, people die in conflicts, and any war situation results in devastation. Advances in technology further increased the scale of warfare and casualties. Nevertheless, the past period of history could not become an example for future generations